Career Path to Nurse Job Satisfaction In The Hospital - Azwar Azwar; Nur Hidayah; Andi Adriana Amal; Syamsiah Rauf (Journal of Health Science and Prevention, 2019)
The high number of nurses who work can illustrate that nurses have an important role in improving health status so that strategic steps are needed in managing nursing staff in a better direction. As for the impact caused by uncontrolled nursing staff is dissatisfaction with nurses nurses so that the decline in nurse performance in providing nursing care to patients so that nurse satisfaction is an indicator that must be considered by all parties concerned. The solution to this problem is the issuance of the Government Regulation of the Republic of Indonesia through the ministry of health which has issued a policy regarding nurses' career paths as an embodiment in improving the quality of nursing staff and is expected to be able to increase nursing staff satisfaction. The writing of this article aims to see how the career path influences the satisfaction of nurses in the hospital. Literature and research review was carried out using several databases: 12 articles from Google Scholar and Pubmed with key words in nurse careers, performance, nurses and nurse satisfaction with career paths. From the results of a review of several journals included in the inclusion criteria, it was found that nurses' career paths had good effectiveness towards increasing nurse satisfaction, this can be seen by the existence of a continuous education system and work rewards that are owned by the career level system.